Imaging in Obstructive Jaundice: What a Radiologist Needs to Know before Doing a Percutaneous Transhepatic Biliary Drainage - Gupta, Pankaj; Gupta, Jyoti; Kumar-M, Praveen (Journal of Clinical Interventional Radiology ISVIR, 2020)
Percutaneous transhepatic biliary drainage (PTBD) is one of the commonly performed biliary interventions. In patients with obstructive jaundice, PTBD may be a lifesaving emergency procedure or may serve as an alternative intervention in patients who fail to undergo endoscopic drainage or those who are too sick to be considered for endoscopic drainage. The key factor in technical and clinical success of PTBD is a thorough preprocedure imaging evaluation. In this review, we highlight the imaging aspects that should be evaluated and reported by a radiologist when evaluating a patient planned for biliary drainage.
Keywords: obstructive jaundice; imaging; percutaneous transhepatic biliary drainage